2013
DOI: 10.1002/grl.50938
|View full text |Cite
|
Sign up to set email alerts
|

Stationarity of the tropical pacific teleconnection to North America in CMIP5/PMIP3 model simulations

Abstract: The temporal stationarity of the teleconnection between the tropical Pacific Ocean and North America (NA) is analyzed in atmosphere‐only, and coupled last‐millennium, historical, and control runs from the Coupled Model Intercomparison Project Phase 5 data archive. The teleconnection, defined as the correlation between December‐January‐February (DJF) tropical Pacific sea surface temperatures (SSTs) and DJF 200 mb geopotential height, is found to be nonstationary on multidecadal timescales. There are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 39 publications
6
77
0
Order By: Relevance
“…This result suggests that the observed sea surface temperature is important for the correct simulation of precipitation at different regions. Nevertheless, some of the differences between the observed and modeled precipitation patterns in the middle and high latitudes may be due to different internal variabilities that are present in the observations and in the AMIP runs (Coats et al 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This result suggests that the observed sea surface temperature is important for the correct simulation of precipitation at different regions. Nevertheless, some of the differences between the observed and modeled precipitation patterns in the middle and high latitudes may be due to different internal variabilities that are present in the observations and in the AMIP runs (Coats et al 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The possible impacts of model biases in last-millennium simulations have been explicitly discussed for only a few specific regional aspects of climate dynamics and variability (e.g., Coats et al, 2013aCoats et al, , 2016aZanchet-tin et al, 2015;Stevenson et al, 2016). A broader assessment of model biases in simulated patterns, variability, and teleconnections would therefore increase our confidence in both climate dynamics and the variability inferred from climate simulations of the last millennium.…”
Section: Opportunities For Modeling Progressmentioning
confidence: 99%
“…Conversion of the proxy into a climatic variable can be achieved through regression or traditional inverse methods as is done with the widely used regional drought atlases (Cook et al, , 2010aPalmer et al, 2015). Nevertheless, in many cases the multivariate nature of proxy data, the presence of large uncertainties and limited spatiotemporal coverage in a calibration proxy network or nonstationary behavior between the proxy predictor and the climate predictand render regression and inversion challenging (e.g., Wilson et al, 2010;Lehner et al, 2012;Smerdon, 2012;Tingley et al, 2012;Coats et al, 2013a;Gallant et al, 2013;Evans et al, 2014;Konecky et al, 2014;Raible et al, 2014;Wang et al, 2014bWang et al, , 2015Konecky et al, 2016).…”
Section: Expectations Of Temporal or Spatial Consistency Betweenmentioning
confidence: 99%
“…Moreover, exploiting teleconnected locations implicitly assumes that the teleconnected relationship does not significantly depend on the external forcing (Batehup et al 2015). Coats et al 2013 found that atmospheric forcing cannot account for the non-stationary teleconnection between tropical Pacific SSTs and 200 mb geopotential height. Gallant et al 2013 found significant variations through time in teleconnections on near-centennial timescales in model simulations forced by internal dynamics alone, but Batehup et al 2015 found that using multiple teleconnected regions minimizes any effects of non-stationarities.…”
Section: Introductionmentioning
confidence: 99%